2022
DOI: 10.1002/2211-5463.13446
|View full text |Cite
|
Sign up to set email alerts
|

KIF2C affects sperm cell differentiation in patients with Klinefelter syndrome, as revealed by RNA‐Seq and scRNA‐Seq data

Abstract: Klinefelter syndrome (KS) is a leading contributor to male infertility and is characterised by complex and diverse clinical features; however, genetic changes in the KS transcriptome remain largely unknown. We therefore used transcriptomic and single‐cell RNA sequencing (scRNA‐seq) datasets from KS versus normal populations through the Gene Expression Omnibus (GEO) database to identify gene biomarkers associated with the occurrence of KS. We identified a total of 700 differentially expressed genes (DEGs) and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…By combining scRNA-seq with bulk RNA-seq data and IHC staining, Winge et al found that such germ cell loss in KS patients might start as early as in the fetal testis 126 . And another study found that KIF2C might be a germ-cell-related gene to regulate spermatogenic development in KS testes 127 . Frankly, based on the current evidence from scRNA-seq data, it's too early to answer the question that what was the transcriptional change in the residual germ cells of KS patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By combining scRNA-seq with bulk RNA-seq data and IHC staining, Winge et al found that such germ cell loss in KS patients might start as early as in the fetal testis 126 . And another study found that KIF2C might be a germ-cell-related gene to regulate spermatogenic development in KS testes 127 . Frankly, based on the current evidence from scRNA-seq data, it's too early to answer the question that what was the transcriptional change in the residual germ cells of KS patients.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the interested genes were not restricted to one gene or several genes, the researchers could detect a gene family (such as Interleukins) or a series of function-related genes (such as inflammatory cytokine receptors) in scRNA-seq data 142 , which could give researchers a view on macroscale. Moreover, an updated usage of this process was to not only show the type of cells that a certain gene was expressed in, but also show its transcriptional changes during spermatogenesis 143 or among different pathological groups 127 , 144 . A good example came from He et al's work 127 , in which they identified four interested genes ( KIF2C , MRPS2 , RPS15 and TSFM ), and then based on human scRNA-seq data of both KS testes and normal testes, they showed that KIF2C were downregulated while RPS15 were upregulated in KS testes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CpG sites annotated to HEN1 methyltransferase homolog 1 ( HENMT1 ), calcyclin-binding protein ( CACYBP ), and GTPase-activating protein ( SH3 domain)-binding protein 1 ( G3BP1 ) genes have been reported within 47XXY-specific loci, suggesting an epigenetic regulation in 47XXY ( Wan et al, 2015 ). Gene expression differences and transcriptomics sequencing have been extensively studied ( Astro et al, 2021 ; Davies, 2021 ; He et al, 2022 ). The azoospermia factor (AZF) microdeletions is considered the most frequent genetic cause of male infertility along with Klinefelter syndrome ( Lahoz Alonso et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…The azoospermia factor (AZF) microdeletions is considered the most frequent genetic cause of male infertility along with Klinefelter syndrome ( Lahoz Alonso et al, 2023 ). Based on RNA-seq and scRNA-Seq data, KIF2C may be closely related to the differentiation and development of sperm cells in 47XXY ( He et al, 2022 ). However, there is still much unknown about how epigenetic regulatory landscape evolve in 47XXY.…”
Section: Introductionmentioning
confidence: 99%